Analysis of the Role of an Innovation Broker Appointed by a Cotton Industry Environmental Innovation Partnership in Queensland, Australia. (September 2014) - Hood, Olive; Coutts, Jeff; Hamilton, Gus
The outcomes of agricultural innovation systems can be viewed as the emergent product of multiple interacting, multilevel, concomitant initiatives of diverse duration. The new language of environmental innovation partnerships, organizational groups and innovation brokers (IBs) engages with this perspective. In the cotton farming systems case analysed here, the participants developed what could be considered to be an innovation partnership, stimulated by an agri-environmental incentive scheme that supported on-farm implementation of environmentally sensitized irrigation practices within a catchment. The participants pooled their resources and appointed a short-term IB to facilitate the 'purchase of knowledge' by local irrigators and their agronomic advisers, relevant to their self-identified irrigation knowledge needs. The IB also facilitated linkages among the partners' various irrigation, water, cotton and catchment initiatives. The partners hypothesized that new or modified organizational groupings would emerge and that system-wide practice changes would result, and that if the new organizational arrangements could be sustained post-project, a legacy of ongoing capability for systemic change could be achieved. This research shows that the short-term objectives were met, but the expected post-project legacy did not emerge. The paper discusses the implications for innovation brokerage and evaluation of such partnerships.